Radiation vulcanization of natural rubber latex loaded with carbon nanotubes - Atieh, Muataz Ali; Nazir, Nazif; Yusof, Faridah; Fettouhi, Mohammed; Ratnam, Chantara Thevy; Alharthi, Mamdouh; Abu-Ilaiwi, Faraj A.; Mohammed, Khalid; Al-Amer, Adnan (Taylor & Francis, 2010)
The radiation vulcanization of natural rubber latex (NRL) has been carried out with 150 keV electrons beam with the presence of carbon nanotubes. The NRL/CNTs were prepared by using solving casting method by dispersing carbon nanotubes in a polymer solution and subsequently evaporating the solvent. The load of the carbon nanotubes in the rubber was varied from 1–7wt%. Upon electron beam irradiation, the tensile modulus of the nanocomposites increases with the increase of carbon nanotubes content up to 7wt%. The nanotubes were dispersed homogeneously in the SMR‐L matrix in an attempt to increase the mechanical properties of these nanocomposites. The properties of the nanocomposites such as tensile strength, tensile modulus, tear strength, elongation at break and hardness were studied.